The effect of Wii Fit exercises on clumsiness and quality of life in children with developmental coordination disorder - ayoub hashemi; mahmoud sheikh; davood homanian; fazlollah bagherzadeh (مجله علوم روانشناختی, 2019)
Background:  Developmental coordination disorder is a neurodevelopmental disorder that can interfere with motor coordination and that causes psychological problems. Research refer to the positive effects of training on sensory and motor functions, but could Wii Fit exercise be effective on clumsiness and quality of life these children?  Aims: The present study aimed to investigate the effect of Wii Fit exercises on clumsiness and the quality of life in children with DCD. Method: The present research was a quasi-experimental study. Using  Willson (2007) developmental coordination disorder questionnaire, 30 children aged 7-12 years with DCD were selected through cluster sampling and placed randomly into two experimental and control groups. In order to evaluate the dependent variables, Bruininks-Oseretsky (1950) test of motor proficiency and Sebir et al. (2007) health related quality of life questionnaire were used. The experimental group received an intervention program for 8 weeks (2 sessions per week, 55 minutes per session). Statistical analysis was performed using multivariate analysis of covariance. Results: The results showed that there was a significant difference between the two experimental and control groups in the variables of clumsiness (F= 14/92, p≤0/001) and quality of life (F= 121/28, p≤0/001). Conclusions: Wii Fit exercises can affect the clumsiness and quality of life of DCD children.